Technology acceptance in electric mobility: A bibliometric review and research agenda - Yotapditya, Igor; Ngatno, Ngatno; Pradhanawati, Ari; Dewi, Reni (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2026)
This study maps the intellectual and conceptual development of technology acceptance research within the electric vehicle (EV) domain using a comprehensive bibliometric science-mapping approach. A total of 272 peer-reviewed Scopus-indexed articles published between 2011 and 2025 were systematically analyzed following the PSALSAR protocol and PICOC framing. Performance analysis and network-based mapping techniques including co-word, bibliographic coupling, co-citation, thematic mapping, and thematic evolution were applied using Biblioshiny and VOSviewer. The results demonstrate rapid publication growth, increasing international collaboration, and consolidation of behavioral acceptance frameworks as the dominant analytical foundation of the field. Technology acceptance model, theory of planned behavior, and UTAUT/UTAUT2 emerge as the central theoretical cores structuring EV adoption research, with recent thematic evolution shifting toward behavioral intention, sustainability orientation, and environmental concern. The study reconstructs conceptual architecture, identifies underexplored behavioral domains, and provides an integrated epistemic foundation for cumulative theory development in electric vehicle technology acceptance research.